Editorial: Whither Or Wither TRC? Special issue: The South African Truth and Reconciliation Commission - Wilbraham, Lindy (PINS-Psychology in Society, 2026)
PINS's (Psychology in society) plan to devote a special issue to the operations and effects of the South African Truth and Reconciliation Commission (TRC) was hatched in 1998. At this stage, the TRC's Committee on Human Rights Violations had completed the harrowing testimony-collection from survivors and produced a report summarising their findings (TRC, 1998); the Committee on Amnesty was embroiled in hearings with perpetrators of politically motivated human rights violations, and in (contentious) judgement about whether the intent and quality of their "truths" warranted their "pardon"; and the Committee on Reparation and Rehabilitation had yet to find a way to begin their work of compensation and healing. Two years on, it is difficult to discern signs of "closure• in any of these realms. This is not to disavow ongoing, well intentioned and committed work within (and without) the TRC process, but to acknowledge the shifts in public discourse that have come to interrogate the map, the route and the destination of the TRC. Thus, what would count as "closure•, and to whom?